1999
DOI: 10.4049/jimmunol.163.6.3516
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Type 1 Cytokine Profile in Bronchoalveolar Lavage T Cells of Patients with Hypersensitivity Pneumonitis

Abstract: Hypersensitivity pneumonitis (HP) is characterized by an inflammatory lymphocytic alveolitis comprised of both CD8+ and CD4+ T cells. Animal models suggest that HP is facilitated by overproduction of IFN-γ, and that IL-10 ameliorates severity of the disease, indicating a Th1-type response. To determine whether a Th1 phenotype in HP also exists clinically, bronchoalveolar lavage (BAL) and peripheral blood (PB) T cells were obtained from HP individuals and analyzed for Th1 vs Th2 cytokine profiles. It was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Naïve CD4 + T cells encounter antigen and can differentiate into T helper (T H ) subsets such as T H 1, T H 2, T H 9, T H 1 7, T H 22, T follicular cells (T FH ), or T regulatory cells (Tregs) and Type 1 regulatory cells (Tr1), depending on signals from the microenvironment. Previous studies were unable to reach a consensus on which T H cell(s) type are important for disease pathogenesis in FLD [28,74,76,85,86,97,98], however, subsequent studies have found a prominent role for T H 17 cells. The presence of lung lymphocytes and granuloma formation are classic hallmarks of FLD, and CD4 + and CD8 + T cells are found in the BAL of patients with FLD, suggesting they play a role in pathogenesis [79].…”
Section: Overview Of Fld Pathogenesis Saccharopolyspora Rectivirgula ...mentioning
confidence: 98%
See 1 more Smart Citation
“…Naïve CD4 + T cells encounter antigen and can differentiate into T helper (T H ) subsets such as T H 1, T H 2, T H 9, T H 1 7, T H 22, T follicular cells (T FH ), or T regulatory cells (Tregs) and Type 1 regulatory cells (Tr1), depending on signals from the microenvironment. Previous studies were unable to reach a consensus on which T H cell(s) type are important for disease pathogenesis in FLD [28,74,76,85,86,97,98], however, subsequent studies have found a prominent role for T H 17 cells. The presence of lung lymphocytes and granuloma formation are classic hallmarks of FLD, and CD4 + and CD8 + T cells are found in the BAL of patients with FLD, suggesting they play a role in pathogenesis [79].…”
Section: Overview Of Fld Pathogenesis Saccharopolyspora Rectivirgula ...mentioning
confidence: 98%
“…However, when DBA/2 mice are given recombinant IL-12 intranasally, they become sensitive to developing FLD [83]. While BAL and blood samples taken from patients with FLD or summer-type HP had elevated IFN-γ levels, it is unclear whether these were patients who were sensitive to S. rectivirgula [98]. The cellular sources of IFN-γ were likened to neutrophils and a small proportion of NK cells, and in the absence of neutrophils there is a reduction of the severity of alveolitis, although the recruitment of immune cells into the lung following S. rectivirgula is not completely eliminated [28], although more recent work suggest that neutrophils may not be important for the development of inflammation in the lung [102].…”
Section: Overview Of Fld Pathogenesis Saccharopolyspora Rectivirgula ...mentioning
confidence: 99%
“…Presentation of foreign antigen by APCs to CD4 + T cells stimulates a predominantly CD4 + Th1 immune response. Correspondingly, presence of lymphocytosis in bronchoalveolar lavage fluid is a useful tool in differentiating HP from other ILDs 37 . This response, mediated by IL‐12 and interferon‐γ, produces CXCL10 to recruit T lymphocytes to the alveolar space, and promote granuloma formation by inducing the functional differentiation and survival of activated macrophages and dendritic cells 38 .…”
Section: Immunopathogenesismentioning
confidence: 99%
“…Correspondingly, presence of lymphocytosis in bronchoalveolar lavage fluid is a useful tool in differentiating HP from other ILDs. 37 This response, mediated by IL-12 and interferonγ, produces CXCL10 to recruit T lymphocytes to the alveolar space, and promote granuloma formation by inducing the functional differentiation and survival of activated macrophages and dendritic cells. 38 The immunologically mediated pathways leading to HP are shared with other granulomatous lung diseases, including chronic beryllium disease and sarcoidosis.…”
Section: Immunopathog Ene S Ismentioning
confidence: 99%